Determinan Agresivitas Pajak dengan Kualitas Audit Sebagai Pemoderasi - Tambun, Sihar; Lestari, Lestari (Universitas 17 Agustus 1945 Jakarta, 2025)
This research succeeded in finding that the digital transformation variable has a negative effect and executive compensation has a positive effect on tax aggressiveness. Meanwhile, the family ownership variable has no effect on tax aggressiveness. This research also succeeded in proving that with audit quality, companies can strengthen the negative relationship between intangible asset variables and tax aggressiveness. Several contributions from this research include first, understanding that audit quality can influence the relationship between one of the independent variables in this research, so that research can be carried out regarding variables that influence corporate tax aggressiveness using new aspects. Second, company management can improve the implementation of intangible asset and executive compensation appropriately, in order to optimize tax aggressiveness in accordance with tax regulations and not violate the law